2017
DOI: 10.3389/fnbeh.2017.00052
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation of the Nucleus Accumbens Core Affects Trait Impulsivity in a Baseline-Dependent Manner

Abstract: Deep brain stimulation (DBS) of the nucleus accumbens (NA) is explored as a treatment for refractory psychiatric disorders, such as obsessive-compulsive disorder (OCD), depressive disorder (MDD), and substance use disorder (SUD). A common feature of some of these disorders is pathological impulsivity. Here, the effects of NAcore DBS on impulsive choice and impulsive action, two distinct forms of impulsive behavior, were investigated in translational animal tasks, the delayed reward task (DRT) and five-choice s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 91 publications
2
9
0
Order By: Relevance
“…For DBS, we used bilateral, monophasic (60 µs pulse width and 130 Hz frequency) stimulation with a constant current of 150 µA. These parameters are consistent with previous studies in the field that used high-frequency stimulation (HFS; [21,[32][33][34]. After a stable level of self-administration was achieved, the effects of DBS on cocaine self-administration in cocaine-dependent rats was evaluated for 4 consecutive days, with 2 "ON" and 2 "OFF" sessions on alternate days.…”
Section: Deep Brain Stimulationsupporting
confidence: 64%
“…For DBS, we used bilateral, monophasic (60 µs pulse width and 130 Hz frequency) stimulation with a constant current of 150 µA. These parameters are consistent with previous studies in the field that used high-frequency stimulation (HFS; [21,[32][33][34]. After a stable level of self-administration was achieved, the effects of DBS on cocaine self-administration in cocaine-dependent rats was evaluated for 4 consecutive days, with 2 "ON" and 2 "OFF" sessions on alternate days.…”
Section: Deep Brain Stimulationsupporting
confidence: 64%
“…In SP-5-CSRTT, time-out periods were signaled by turning on the house-light. Despite this, behavioral challenges, such as varying ITI or SD, resulted in similar effects to conventional 5-CSRTT (Bari et al 2008; Saund et al 2017; Schippers et al 2017). Varying the ITI led to increased premature responding and decreased omissions.…”
Section: Discussionmentioning
confidence: 94%
“…Varying the ITI led to increased premature responding and decreased omissions. Increasing ITI durations has previously been reported to lower omissions in rats (Schippers et al 2017), yet increases in omissions have also been shown (Chudasama et al 2003; Saund et al 2017). This may result from shorter limited hold periods urging faster responses following stimulus presentation.…”
Section: Discussionmentioning
confidence: 96%
“…In the NAc, HI animals present a decreased availability of D1 and D2/3 receptors and of dopamine transporter (DAT) (Caprioli et al, 2015, Jupp et al, 2013) as well as a reduction in grey matter density (Caprioli et al, 2014). Interestingly, deep brain stimulation in the NAc decreases impulsivity particularly in HI animals (Schippers et al, 2017). The NAc has been involved in chronic pain – see for review (Benarroch, 2016, Mitsi and Zachariou, 2016) – and appears as a prime candidate to mediate decision-making and motivational alterations observed in chronic pain models.…”
Section: Discussionmentioning
confidence: 99%